Sensitivity of pancreatic cancer cells to chemotherapeutic drugs, signal transduction inhibitors and nutraceuticals can be regulated by WT-TP53. (January 2021) - Abrams, Stephen L.; Akula, Shaw M.; Martelli, Alberto M.; Cocco, Lucio; Ratti, Stefano; Libra, Massimo; Candido, Saverio; Montalto, Giuseppe; Cervello, Melchiorre; Gizak, Agnieszka; Rakus, Dariusz; Steelman, Linda S.; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic malignancy. Approximately 85% of pancreatic cancers are classified as PDACs. The survival of PDAC patients is very poor and only 5–10% of patients survive 5 years after diagnosis. Mutations at the KRAS and TP53 gene are frequently observed in PDAC patients. The PANC-28 cell line lacks wild-type (WT) TP53. In the following study, we have investigated the effects of restoration of WT TP53 activity on the sensitivity of PANC-28 pancreatic cancer cells to various drugs which are used to treat PDAC patients as well as other cancer patients. In addition, we have examined the effects of signal transduction inhibitors which target critical pathways frequently deregulated in cancer. The effects of the anti-diabetes drug metformin and the anti-malarial drug chloroquine were also examined as these drugs may be repurposed to treat other diseases. Finally, the effects of certain nutraceuticals which are used to treat various ailments were also examined. Introduction of WT-TP53 activity in PANC-28 PDAC cells, can increase their sensitivity to various drugs. Attempts are being made clinically to increase TP53 activity in various cancer types which will often inhibit cell growth by multiple mechanisms.